Innovations and Their Effects on One Tambon One Product (OTOP) Enterprises’ Performance in Thailand - Suwannapusit, Ubonwan; Chayomchai, Ampol (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The objective of this research is to study the four aspects of innovations, including product innovation, process innovation, management innovation and marketing innovation, which affected Thailand OTOP enterprises’ financial and non-financial performance. The population of the research comprised 75,619 Thailand OTOP enterprises in the year 2014. Sample size consisted of 382 enterprises recruited from all parts of Thailand. The data collection tool of this study was questionnaire. Descriptive statistics and multiple regression analysis were executed. Results revealed that (1) the innovations in all aspects of the OTOP enterprises were high and all aspects of their performance were increasing, (2) product and process innovations had positive significant effects on all aspects of financial performance, (3) product innovation, process innovation and management innovation had positive significant effects on all non-financial performances, (4) marketing innovation influenced the performance in these aspects including profit, debt and marketing, and (5) the regression coefficient of determination was not very high. The research suggested that OTOP enterprises should develop all aspects of innovations because innovations were the key factors that affected the performance and the success of OTOP enterprises.